Incineration of Hazardous and Toxic Waste and Its Impact on Public Health in Indonesia - Khafizah Valerina Akhmadi; Zaskia Amalia Putri; Irmayanti; Radit (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: Hazardous and toxic waste management (B3) is a major challenge in protecting the environment and public health. Incineration technology is known to be effective in reducing the volume of B3 waste by 80-90% and destroying hazardous substances. However, this process also has the potential to produce hazardous emissions of hazardous compounds such as dioxins, furans, and toxic metals that can potentially harm human health and the environment if not managed according to standards. Objective: The aim of this study is to provide the effectiveness, benefits, challenges, and public health impacts of the hazardous and toxic waste (B3) incineration process in Indonesia. Methods: This study uses a literature review methodology to evaluate the benefits, challenges, and health impacts of incineration technology in B3 waste management, focusing on a case study in Indonesia. Results: The results show that incineration can function effectively if supported by adequate emission control technology and appropriate regulations. Conclusion: The implementation of emission control standards and strict supervision are key to minimizing the risk of pollution and health impacts, so that sustainable and safe B3 waste management can be achieved.